2002
DOI: 10.1182/blood.v100.1.299
|View full text |Cite
|
Sign up to set email alerts
|

Intersubunit circular permutation of human hemoglobin

Abstract: For many years, human hemoglobin (Hb) isolated from erythrocytes has been investigated as a potential oxygen delivery therapeutic. Advantages with respect to the need for blood typing were balanced with various undesirable properties of cell-free Hb, including cost, overall oxygen affinity, alterations in cooperativity, and ready dissociation into toxic dimeric species. The use of total gene synthesis has resulted in very high levels of functional human Hb expression in Escherichia coli, but there remains a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…Membrane-bound hemoglobin was measured using the pyridine hemochromagen assay of Sanders et al [38] . To quantify the spectrin present, ghosts were prepared from washed erythrocytes as described above and then treated with solubilisation buffer (125 mM Tris-HCl pH 6.8; 4% SDS; 20% glycerol; 10% 2-mercaptoethanol) and heat denatured at 95 °C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Membrane-bound hemoglobin was measured using the pyridine hemochromagen assay of Sanders et al [38] . To quantify the spectrin present, ghosts were prepared from washed erythrocytes as described above and then treated with solubilisation buffer (125 mM Tris-HCl pH 6.8; 4% SDS; 20% glycerol; 10% 2-mercaptoethanol) and heat denatured at 95 °C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Precedent for this idea comes from the work of Sligar and co-workers, who reported the circular permutation of a di-α-globin sequence to yield a functional Hb (36). Our laboratory has shown previously that relocating the termini in swMb to the G-H loop by circular permutation does not appear to significantly alter the structure of the heme binding pocket or its ligand binding properties (37).…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that ligand binding to the α-cp β dimer exhibits almost identical properties (Figure 6). Sanders et al (36) reported that a recombinant hemoglobin derived from a circularly permuted di-α-chain associated with two wild-type β -globin subunits has an increased O 2 affinity ( P 50 = 0.9 mmHg) and decreased cooperativity ( n = 2.0) compared to HbA. The higher cooperativity of this permuted di - α - β 2 hemoglobin, compared to α-cp β is likely achieved as a result of stable quaternary contacts between the four globin subunits, which are not present in a dimer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These alternatives to BU treatment may solve problems and become breakthroughs for stem cell transplantation in patients with advanced disease. Indeed, recent reports show favorable allogeneic transplantation outcomes using intravenous or targeted oral BU conditioning regimens [23, 24, 25]. …”
Section: Discussionmentioning
confidence: 99%